LITHIUM AND ITS ISOTOPES IN MAJOR WORLD RIVERS: IMPLICATIONS FOR WEATHERING AND THE OCEANIC BUDGET - Huh Y.; Edmond J.M.; Chan L.H.; Zhang L. (My University, 1998)
The outstanding problem in the lithium geochemical cycle is the lack of an isotopic mass balance in the ocean. The δ6Li compositions of fresh basalts (−4‰), the hydrothermal fluids derived from them (average −9‰), and seawater (significantly heavier at −32‰) are well understood, but only very sparse river input data are available for Li mass balance calculations. In an attempt to rectify the situation we have measured the lithium concentrations and isotopic compositions of major world rivers draining representative geological terrains. This helps both to constrain the river endmember and to understand the behavior of lithium isotopes in the continental weathering environment. Fluvial isotopic compositions display a very large range, −6.0 to −32.2‰. There is no definitive relationship between δ6Li and lithology but, in general, rivers draining marine evaporites are −20 to −22‰, carbonates −26 to −32‰, black shales −26‰, shields −6.6 to −19‰, and mixed siliceous terrains −6 to −28‰. The flow-weighted mean concentration of the measured rivers is 215 nM at −23‰. This updated riverine δ6Li value, responsible for ∼30% of the global riverine discharge, does not solve the isotopic imbalance if the measured Li concentrations and isotopic compositions are representative of all rivers. The presence of a yet unidentified sink with a higher fractionation factor (α ≈ 1.023) than determined for low temperature basalt alteration (α = 1.019) is required for an isotopic steady-state of Li in the ocean. Authigenic clays are a possible candidate as clays are known to be enriched in both lithium and in the light isotope preferentially. Alternatively, the hydrothermal flux must be much less than half of that estimated by the 3He inventory and the oceanic budgets for 87Sr/86Sr and Mg. The relationship of δ6Li to the major ions and 87Sr/86Sr suggests that the important processes affecting river dissolved lithium isotopic compositions are fractionation between solution and secondary minerals and thus the intensity of weathering.